Histochemical and Anatomical Studies of Phloem and Xylem Cells of Jackfruit (Artocarpus heterophyllus Lam.) Tree - Islam, MA; Begum, S (International Journal of Natural Sciences, 2012)
The localization of starch, lipid and protein, nuclei in the phloem and xylem cells of stem of Jackfruit trees (Artocarpus heterophyllus) has been studied. The optical digital images of anatomical features and localization of nuclei and reserve materials were obtained by light microscopy and fluorescence microscopy. Starch granules in the ray parenchyma cells were more abundant in the outer xylem close to the cambium than in the inner xylem and phloem. Radial localization of starch granules provided more clear data than transverse and tangential observations. Lipid and protein appeared as droplets and were uniformly distributed in the outer xylem. The parenchyma cells of phloem have large amount of lipid bodies but those were almost absent in cambium and xylem ray parenchyma cells. The results on the localization of storage starch, lipid droplets and proteins in phloem, cambium and xylem cells indicating that reserve materials might be important for wood formation in jackfruit trees. This data would be helpful for further study in tree breeding program and clarification of the mechanism of utilization of such reserve materials and their distribution pattern within the cells. DOI: http://dx.doi.org/10.3329/ijns.v2i1.10876 International Journal of Natural Sciences (2012), 2(1): 01- 07